Seasoned equity offerings and differences in share-price impact by firm categories - Saeed Md. Abdullah; Simon Zaby (International Journal of Financial Studies, 2021)
The seasoned equity offering (SEO) market plays a significant role in the economic development of a country by providing liquidity for ongoing commercialization and innovation. This study is a comprehensive analysis of 149 SEOs and their effect on share prices in Thailand between 2009 and 2019. SEOs are categorized based on their time categories (early, mid, and grown) and volume categories (small, medium, big, and super). Using the event study methodology (multi-factor model), we find that most SEOs under both categories have a negative cumulative abnormal return (CAR) in the window period. Ranking the types of SEOs reveals that grown SEOs have the highest proportion of negative CAR under the time categories. Under the volume categories, medium SEOs show the largest share. The results were validated by regression assumption tests provided by Gnu Regression, Econometrics and Time-series Library, and correspond to established theories. The paper also contains an extensive literature review of studies examining the link between SEOs and share-price development. Our findings have important implications for corporations, investors, and regulatory bodies and can thus help in increasing market confidence for sustainable corporate funding.
Keywords: 330; SEO; seasoned equity offering; asset pricing; corporate finance; sustainable finance